Digital Transformation Management and School Performance Governance: A Case Study of Transparency and Accountability in Primary Schools - Nurul Faizah; Ahwy Oktradiksa; Muhammad Tohirin (Universitas Nurul Jadid, 2026)
Digital transformation in school governance has become a strategic imperative in contemporary education management, yet the mechanisms through which it enhances transparency and accountability in school performance management remain insufficiently understood. This study aims to analyze how digital transformation management contributes to transparency and accountability in primary school performance governance, identify the barriers that constrain its development, and examine the strategies schools employ to optimize its implementation. A qualitative case study design was adopted, with data collected through in-depth interviews, field observation, and documentation review across three private primary schools at different stages of digital maturity. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that digital transformation operates as a graduated organizational process rather than a technological event, determined by the coherence between leadership commitment, staff readiness, and governance design. Digital systems enhanced transparency through structured, multi-channel stakeholder disclosure and strengthened accountability by converting professional activity into retrievable, verifiable evidence. The most consequential barriers were human rather than technological, and effective strategies were those calibrated to each institution's specific constraint profile. The implications of this study suggest that education policymakers and school leaders must reorient digital transformation initiatives away from tool provision and toward the deliberate development of human capacity, governance culture, and institutional systems that embed transparency and accountability as organizational values rather than compliance obligations.